Staff Studies for the World Economic Outlook. (World Economic and Financial Surveys; World Economic and Financial Surveys ;, 1986)
This paper reviews recent analytical and empirical research on the determination of employment, to provide a framework for evaluating the merits of alternative policies to cope with unemployment. Particular emphasis is placed on the mechanisms of employment and wage determination described in recent studies. The lack of any systematic relationship between countries' long-run growth and employment performances reflects the fact that output per person employed (labor productivity) or, conversely, the labor intensity of production, has developed quite differently across countries. The main mechanism through which the rise in real wages has prevented greater employment gains in Europe over the past ten to fifteen years seems to have been a substitution of capital for labor which has lowered the labor intensity of production significantly more than in the United States. There are a number of important caveats with respect to the apparent relationship between differences in employment and labor cost developments across countries.